Pengaruh Penambahan Limbah Styrofoam Terhadap Karakteristik Campuran AC-WC - Jacksen Rante Lebang; Rais Rachman; Alpius (Paulus Civil Engineering Journal, 2022)
This study was conducted to find out the characteristics of the mixture with the addition of Styrofoam waste in the AC-WC mixture. The test was marshalled. From the results of testing on the AC-WC mixture with the addition of styrofoam waste, conventional marshall method obtained mixed characteristics with stability, flow, VIM, VMA and VFB values that have qualified in bina marga standard 2018. Styrofoam waste greatly affects the values of stability, flow, VIM, VMAs, and VFBs. The use of styrofoam waste levels that makes the cavity in the mixture becomes small so that the mixture can be more resistant to water, but the strength of the mixture decreases due to increasing levels of Styrofoam waste so that the cavity in the mixture is filled with styrofoam waste grains that have dissolved and mixed with asphalt which resulted in asphalt is not effective in binding aggregates so that the strength of the mixture becomes reduced.